Comparison of Microfracture with Extracellular Matrix Augmentation and Osteochondral Autograft Transplantation for the Treatment of Medium-Size Osteochondral Lesions of the Talus. Issue 4 (22nd October 2020) - Hansen, Oliver B.; Eble, Stephanie K.; Cabe, Taylor; Patel, Karan A.; Deland, Jonathan T.; Sofka, Carolyn M.; Drakos, Mark C.
Category: Ankle; Arthroscopy; Basic Sciences/Biologics Introduction/Purpose: Historically, microfracture has been used to treat small talar osteochondral lesions (OLTs) with good results, while osteochondral autologous transplantation (OAT) has proven superior for the treatment of larger lesions. It is not clear which method is more effective for medium-sized lesions, around the critical size of 150 mm2 above which microfracture outcomes tend to be poor. While OAT carries the risk of co-morbidity at the knee and often requires a malleolar osteotomy, it is thought to result in superior repair tissue compared to microfracture by introducing native hyaline cartilage to the ankle. Microfracture, in contrast, results in the formation of structurally inferior fibrocartilage. The purpose of this study was to determine the relative benefits of OAT and microfracture in the treatment of medium-sized OLTs. Methods: Patients treated for an OLT with OAT or microfracture by a single surgeon fellowship-trained in foot and ankle orthopedics between 2015 and 2018 were screened. Both OAT and microfracture techniques were augmented with a mixture of extracellular matrix and bone marrow aspirate concentrate (ECM-BMAC) for every case included in this study. Patients treated without ECM-BMAC were excluded. Only patients with a lesion size between 80 and 165 mm 2 were included. Minimum follow-up was 12 months. Clinical outcomes were collected in the form of FAOS or PROMIS scores, depending on departmental standards at the time of treatment. MRIs were collected for radiographic analysis of cartilage repair tissue. MRIs were scored using the MOCART system by a fellowship trained radiologist and were also evaluated for the presence of cysts and edema. Patient charts were reviewed to determine rates of revision surgery and therapeutic injection for pain. Results: 52 patients were identified who fit inclusion criteria. 27 of these patients received microfracture and 25 received OAT. The average lesion size for all patients was 117.5 mm2. Patients treated with OAT had significantly higher average total MOCART scores (69 vs. 55, p = 0.04) and significantly lower rates of cyst (14% vs. 55%, p <0.01), edema (59% vs. 90%, p = 0.04), revision surgery (0% vs. 19%, p = 0.05), and therapeutic injection for pain (4% vs. 30%, p = 0.03) compared to patients treated with microfracture. No significant differences were detected in patient reported outcome scores between groups for either FAOS or PROMIS. Age, BMI, lesion size, lesion location, and follow-up time were statistically indistinguishable between groups. Conclusion: In treating OLTs, the native hyaline cartilage introduced by OAT appears to result in higher quality repair tissue when compared to microfracture, as evidenced by OAT patients' higher MOCART scores and lower rates of cyst and edema. This advantage was also reflected in the fact that OAT patients required revision surgery and therapeutic injection for pain less frequently than did microfracture patients. OAT may offer benefits over MF that outweigh its greater risk of comorbidity when addressing medium-sized OLTs.